RATE EVALUATION OF URBAN PUBLIC TRANSPORT (ANGKOT) CASE STUDY: BANDUNG CITY - Aziz, Indrajathie
People need to meet their needs to stay alive, if their needs are not met where they are, then people need to move to meet their needs in other places, this causes congestion in the city, especially the city of Bandung. This study aims to examine the angkot rates in the city of Bandung, to find the sensitivity level of rates changes to the probability of using public transportation modes and to find the ideal rates based on ability to pay & willingness to pay, vehicle operating cost and Dishub regulations. For the analysis of the willingness and ability of consumers, they are divided into two categories, namely respondents who use a car and those who use motorbikes, for vehicle operating costs only based on three routes from Kopamas. From the results of the analysis, it was concluded that the ability to pay of respondents who use cars is greater than the applicable rates in public transportation, which is Rp. 7.498 per passenger, while respondents who use motorbikes have a value of Rp. 6.797 per passenger, the same applies to willingness to pay of Rp. 5.500 per passenger for respondents who use a car and Rp. 11.000 per passenger for respondents who use motorbikes, Of the two modes, the motor mode has the highest sensitivity because it has a greater willingness to pay value than the car's willingness to pay. Meanwhile, the vehicle operating costs for the three Kopamas angkot routes have Rp. 1.712 per angkot - km, Rp. 1.720 and Rp. 2.061, respectively. for the assumption of a load factor of 70%, the rates that come out are Rp. 3.440 per passenger, Rp. 3.229 per passenger and Rp. 4.174 per passenger, so that by analyzing the income (fare box ratio) the rates of Rp. 4.174 per passenger has a higher profit rate than the other tariffs, namely 1.03. Then the applicable existing tariff, which is Rp. 4,000 per passenger, is below the value of vehicle operating costs are so large that they have no profit, so an ideal tariff of Rp. 5.000 is needed, the value of which is above the value of vehicle operating costs, which is Rp. 4.174 per passenger. So Rp 4.500 per passenger can be considered the ideal rate because apart from being at the BOK value, it does not exceed ATP & WTP